Frequent molecular subtype switching and gene expression alterations in lung and pleural metastasis from luminal A-type breast cancer - Klebe, Max; Fremd, Carlo; Kriegsmann, Mark; Kriegsmann, Katharina; Albrecht, Thomas; Thewes, Verena; Kirchner, Martina; Charoentong, Pornpimol; Volk, Nadine; Haag, Johannes C.; Wirtz, Ralph; Oskarsson, Thordur; et al. (JCO precision oncology, 2020)
PURPOSEConversion of tumor subtype frequently occurs in the course of metastatic breast cancer but is a poorly understood phenomenon. This study aims to compare molecular subtypes with subsequent lung or pleural metastasis.PATIENTS AND METHODSIn a cohort of 57 patients with breast cancer and lung or pleural metastasis (BCLPM), we investigated paired primary and metastatic tissues for differential gene expression of 269 breast cancer genes. The PAM50 classifier was applied to identify intrinsic subtypes, and differential gene expression and cluster analysis were used to further characterize subtypes and tumors with subtype conversion.RESULTSIn primary breast cancer, the most frequent molecular subtype was luminal A (lumA; 49.1%); it was luminal B (lumB) in BCLPM (38.6%). Subtype conversion occurred predominantly in lumA breast cancers compared with other molecular subtypes (57.1% v 27.6%). In lumA cancers, 62 genes were identified with differential expression in metastatic versus primary disease, compared with only 10 differentially expressed genes in lumB, human epidermal growth factor receptor 2 (HER2)-enriched, and basal subtypes combined. Gene expression changes in lumA cancers affected not only the repression of the estrogen receptor pathway and cell cycle-related genes but also the WNT pathway, proteinases (MME, MMP11), and motility-associated cytoskeletal proteins (CK5, CK14, CK17). Subtype-switched lumA cancers were further characterized by cell proliferation and cell cycle checkpoint gene upregulation and dysregulation of the p53 pathway. This involved 83 notable gene expression changes.CONCLUSIONOur results indicate that gene expression changes and subsequent subtype conversion occur on a large scale in metastatic luminal A-type breast cancer compared with other molecular subtypes. This underlines the significance of molecular changes in metastatic disease, especially in tumors of initially low aggressive potential.